The impact of non-invasive brain stimulation and digital intervention on social cognitive therapy in autism spectrum disorder: a systematic review and network meta-analysis - Juhao Hou; Yi Fang; Yue Wang; Shilin Wen (Frontiers in Psychiatry, 2026)
Introduction To evaluate the relative efficacy of non-invasive brain stimulation (NIBS) and digital interventions for improving social cognition in autism spectrum disorder (ASD). Methods A systematic search of PubMed, Embase, Web of Science, Cochrane, CNKI to February 2026 yielded 50 randomized controlled trials (RCTs). A Bayesian network meta-analysis was performed using R, ranking interventions via Surface Under the Cumulative Ranking curve (SUCRA) and assessing evidence certainty with Confidence in Network Meta-Analysis (CINEMA). Results Across the included trials (mean age range: 2.54 to 20.80 years), among 9 interventions, transcranial direct current stimulation (tDCS) emerged as optimal (SUCRA = 88.24%), significantly outperforming treatment as usual (TAU) (SMD=-1.69, 95% CrI: -2.67, -0.70). This was followed by high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) (84.38%, SMD=-1.60, 95% CrI: -2.32, -0.89), low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) (74.22%, SMD=-1.36, 95% CrI: -1.77, -0.96), and theta-burst stimulation (TBS) (64.21%, SMD=-1.19, 95% CrI: -2.02, -0.35); all significantly outperformed TAU. Standalone digital interventions ranked lower. Meta-regression showed no significant age moderating effect. Conclusions tDCS is the most efficacious standalone intervention for ASD social cognitive deficits. We recommend tDCS or TBS clinically and advocate a synergistic paradigm integrating NIBS neural priming with digital training. However, future large-scale, rigorous RCTs are required to further validate both these standalone modalities and the proposed combined protocols. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420261337491 , identifier CRD420261337491.